Tanggung Gugat Dokter Atas Kelalaiannya Dalam Menyampaikan Informed Conset Dan Hasil Operasi Yang Tidak Sesuai Dengan Keinginan Pasien - Bezaleel Nugara Santoso (SAPIENTIA ET VIRTUS, 2018)
The society is not only an object of healt enforcement, but also a subject. Therefore, the enforcement of health services is a joint responsibility of the health care providers and the health care recipients. In the application of the profession, a doctor cannot be separated from the health law. However, it is important to acknowledge that a doctor is a common human being who can also make mistakes or commit malpractice in doing his job. A doctor can be hold responsible on the criminal law, civil law, and administrative law. In civil law, a doctor can be hold responsible based on a law violating act and breach of contract. Breach of contract happens when one of the party does not perform what is promised, perform what is promised later than it is supposed to be, perform what is promised below the expectation promised. Meanwhile, an action is considered violating the law when it fulfills the four criteria such as the existence of an action againt the law, there must be a mistake, there must be a loss/damage caused by the action, and there must be a causal relation between the action and the loss/damage. A law violating act does not only mean violating the regulations, but also failing to do the law obligation of the perpetrator, violating other people’s subjective rights, violating the ethics, and violating decency, accuracy and circumspection.